Baseline of the projection under a structural change in energy demand. (November 2016) - Sakamoto, Tomoyuki; Takase, Kae; Matsuhashi, Ryuji; Managi, Shunsuke
Abstract: This article investigates the long-term energy demand and energy policy measures when undergoing structural changes in energy demand. Initially, the statistical test shows the possibility of the structural change from the late 2000s. Therefore, we developed the energy demand model to forecast the energy demand by 2030 that considers the structural change. The results show that there may be a 12% reduction in the energy demand in 2030 compared to the reference case in the Japanese government's outlook, which is equal to about 86.0% of the effect of the planned policy measures by the government, but also that it is difficult to achieve energy-originated CO2 emissions in the national target. Our analysis suggests that mitigation policies are required, but those in the planned policy measures are not completely required to achieve the goal. Highlights: The structural change in energy demand was undertaken beginning in the late 2000s in Japan. We developed the energy demand model and project the future energy consumption considering the structural change. Our model forecasts a 12% reduction in the energy demand in 2030 compared to the reference case in the government's outlook. The demand reduction is equal to about 86.0% of the effect of the planned policy measures by the government.